Microbial lipopeptide production and purification bioprocesses, current progress and future challenges. Issue 7 (21st June 2017) - Coutte, François; Lecouturier, Didier; Dimitrov, Krasimir; Guez, Jean‐Sébastien; Delvigne, Frank; Dhulster, Pascal; Jacques, Philippe
Abstract: Lipopeoptides are amphiphilic compounds combining interesting physicochemical properties and biological activities. Due to their high foaming capacity in aerated bioreactor, the development of scalable bioprocesses for their production is a major bottleneck. In addition, the genes involved in the biosynthesis of these lipopeptides are mainly regulated by the quorum sensing, a global regulatory mechanism depending on cell density and known to be activated in biofilms. Several approaches have thus been considered in literature taking into account two criteria, on one side, to favor, control or avoid foam formation and on the other side, to use planktonic or immobilized (biofilm) cells. These different bioprocesses are discussed in the present review along with the purification strategies proposed for extracting and concentrating these biosurfactants. Abstract : Lipopeptides are amphiphilic compounds combining interesting physicochemical properties and biological activities. Due to their high foaming capacity in aerated bioreactor, the development of scalable bioprocesses for their production is a major bottleneck. In addition, the genes involved in the biosynthesis of these lipopeptides are mainly regulated by the quorum sensing, a global regulatory mechanism depending on cell density and known to be activated in biofilms. Several approaches have thus been considered in literature taking into account two criteria, on one side, to favor, control or avoid foam formation and on the other side, to use planktonic or immobilized (biofilm) cells. These different bioprocesses are discussed in the present review along with the purification strategies proposed for extracting and concentrating these biosurfactants.